Thermospheric damping response to sheath‐enhanced geospace storms. Issue 7 (15th April 2013) - Knipp, D.; Kilcommons, L.; Hunt, L.; Mlynczak, M.; Pilipenko, V.; Bowman, B.; Deng, Y.; Drake, K.
Abstract : [1] We show evidence that solar wind density enhancements and pressure pulses can lead to intense low‐energy particle precipitation and an associated, but unexpected, damping of thermospheric density response. Ground‐based indices, used as proxies for thermospheric energy deposition, fail to capture these interactions in forecasting algorithms. Superposed epoch comparison of a group of poorly specified neutral density storms suggests an event‐chain of (1) multi‐hour, pre‐storm solar wind density enhancement, followed by solar wind dynamic pressure pulses that trigger excess low‐energy particle flux to the upper atmosphere; (2) enhanced production of thermospheric Nitric Oxide (NO) by precipitating particles and storm heating; (3) NO infrared cooling and damping of the thermosphere; and (4) mis‐forecast of neutral density. In the control storms, these features are absent or muted. We discuss the roles of solar wind pre‐conditioning and solar cycle dependency in the problem storms. These problem neutral‐density storms reveal an element of "geo‐effectiveness" that highlights competition between hydrodynamic aspects of the solar wind and other interplanetary drivers. Key Points: Some sheath‐driven storms induce rapid production of thermospheric nitric oxide Infrared nitric oxide emission competes with storm‐driven energy deposition Resulting thermospheric